Knowledge, attitude and practice of generic medicines among doctors in a tertiary care teaching hospital of Tripura, India - Bhattacharjee, Prithul; Das, Lakshman; Ghosh, Ranjib; Das, Uttam K.; Chakraborty, Maitrayee (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The assessment of doctors’ perceptions and understanding about generic medicines may help in recognizing possible barriers to greater generic medicine usage. The primary objective of this study was to explore the knowledge, attitude, and practice (KAP) of doctors toward generic medicines. Methods: A questionnaire based cross-sectional study was carried out in a tertiary-care teaching hospital of Tripura. The questionnaire was designed to assess the KAP about generic medicines. The doctors working in this institute during the study period were included. All data were analysed using statistical software for epidemiology (EPI6). P <0.05 was considered statistically significant. Results: 67.5% doctors agreed to the fact that generic medicines were intended to be interchangeable with a branded drug (p=0.0003). Among the doctors, 95% were aware that generic drug manufacturers need to conduct studies to show bioequivalence between the generic medicine and their branded counterparts (p <0.0001). Majority of the doctors (82.5%) were of the view that generic medicines were as safe as that of branded drugs (p <0.0001). 97.5% of the doctors agreed that importance of generic medicines should be taught in early part of internship. 75% doctors did not think that switching a patient from a brand-name to generic drug may change the outcome of the therapy (p <0.0001). 92.5% doctors said that they prescribe generic medicines (p <0.0001). Conclusion: The study showed that the doctors were well aware of generic medicines and Jan Aushadhi scheme of Govt. of India. It was also observed that efficacy, safety and quality profile of the medicine were the most important factors considered by doctors when they prescribe drugs.